O abuso sexual na infância e o processo de ensino-aprendizagem - Borges, Rozilda Gonçalves (2012)
The research conceptualizes, discusses and briefly recounts the history of childhood sexual abuse. It also surveys the possible pathologies caused by sexual abuse, leading to the treatment both in psychopedagogical clinics and in schools. In order to overcome the trauma, it also seeks help in multidisciplinary teams (psychologists, psychiatrists and others) according to the needs pointed out by the sexually abused child. A survey of the childrens´s life history and sexual abuse was carried out among the ones who participated in social research at the psychopedagogical clinic and at the school. In the psychopedagogical clinic, the sexually abused child who was part of the research participated in 10 sessions of Operative Interviews - EOCA, which is a system of verification of hypotheses for possible difficulties faced by the child. The interview length is about 60 (sixty) minutes, the child participates in Psychopedagogical texts that survey family, school and personal issues. Also, Piagetian tests are done, aiming to identify the level of childrens´s intellectual development. After that, the intention is to outline new teaching and learning approaches for the sexually abused child who suffered the education impacts of the sexual abuse. This study aims to make them enthusiastic again with education. The family participates in the anamnesis interview, which purpose is to know some facts of the child´s life history such as pregnancy, childbirth, nutrition, sleep, psychomotor development, sphincters, language disorders, toys, education, sexuality, relationships and personal characteristics. This information assists the diagnose with dimensions of past, present and future. The interview is usually held with the parents or guardians who know and the child´s life history. This research shows that childhood sexual abuse has different impacts on child´s life but it also shows that when abused children have the appropriate assistance, they can overcome the trauma and fell enthusiasm toward education and life.